The Role of Chinese Music in Shaping Students’ Creative Thinking - Jing Qi (Educational Process: International Journal)
Background/purpose – The process of shaping students’ creative thinking in modern society takes on a new, deeper, and broader dimension. Therefore, studying the role of Chinese music in developing the creativity of primary, secondary, and tertiary education students is deemed relevant. The purpose of this study was to comprehend ways of forming creative thinking of students through the study of Chinese music.